Identifying Neural Biomarkers of Confirmation Bias - Singh, Avinash; Liu, Jia; Voinov, Alexey; Lin, Chin-Teng (The ... International Winter Conference on Brain-Computer Interface, 2025)
It has been observed that individuals prefer to favour information that strengthens their beliefs or values, while information that contradicts them causes unpleasant feelings and is more likely to be ignored. This is known as confirmation bias, and it is usually difficult to dislodge once affirmed. Confirmation bias has been shown to lead to flawed decisions in political, organizational, financial and scientific domains. To better understand the origins and detection of neural biomarkers for confirmation bias, this article presents a study that employed electroencephalography (EEG) signals from 10 participants. The study revealed an apparent increase in theta activity (phase-resetting) and prediction error negativity (PEN) among participants exhibiting confirmation bias. These findings have the potential to contribute to the development of novel brain-computer interface systems capable of detecting confirmation bias. Such systems may help mitigate social polarization and the negative effects of biased decision-making.